Lithium based ceramic materials and membranes for high temperature CO2 separation - Nair, Balagopal; Burwood, Ryan; Goh, Valerie; Nakagawa, K.; Yamaguchi, T. (Elsevier Ltd, 2009)
The selective removal of CO2 at high temperature is a topic of great significance owing to its use in managing CO2 emissions to the atmosphere as well as in enhancing the efficiency of several catalytic processes where CO2 is a product. CO2 absorbent materials and CO2 separating membranes made of lithium based ceramics have been applied to the selective separation of CO2 from gas mixtures. In this review, a summary of the recent progress made in the processing and application of these materials and membranes will be given. The characteristics of the materials and the factors influencing their properties will be examined in detail. Critical issues will be discussed with a view to provide clues for future developments.